Civic universities and bottom-up approaches to boost local development of rural areas: The case of the University of Macerata - Tomasi Sabrina; Cavicchi Alessio; Aleffi Chiara; Paviotti Gigliola; Ferrara Concetta; Baldoni Federica; Passarini Paolo (Agricultural and Food Economics, 2021)
The aim of this paper is to provide a review of the main roles HEIs can play in rural areas. A longitudinal case study about the civic engagement of the University of Macerata - UNIMC (Italy) is presented, by assessing its attempt to fulfil its third and fourth mission through the application of the Quadruple Helix and 3 Model and by implementing the Civic University's dimensions. Furthermore, these aspects have been investigated through the university-business collaboration and the community-academic-collaboration frameworks. More specifically, the paper focussed on UNIMC's commitment at a local level analysing its involvement in local and international projects for place and agri-food product marketing, place branding and rural development, promoted by a research team within the Department of Education, Cultural Heritage and Tourism.
Keywords: 330; Civic university; Co-creation; Quadruple Helix; Rural areas; Sustainable development